2002
DOI: 10.1073/pnas.052025899
|View full text |Cite
|
Sign up to set email alerts
|

The lipofuscin component A2E selectively inhibits phagolysosomal degradation of photoreceptor phospholipid by the retinal pigment epithelium

Abstract: Daily phagocytosis of spent photoreceptor outer segments is a critical maintenance function performed by the retinal pigment epithelium (RPE) to preserve vision. Aging RPE accumulates lipofuscin, which includes N-retinylidene-N-retinylethanolamine (A2E) as the major autofluorescent component. We studied the effect of physiological levels of A2E in RPE cultures on their ability to phagocytose outer segments. A2E localized to lysosomes in cultured RPE as well as in human RPE in situ. A2E-loaded RPE cells in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
192
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(210 citation statements)
references
References 29 publications
14
192
1
3
Order By: Relevance
“…We have previously shown that A2E affects neither the binding nor internalization of OS by RPE cells (8). Immediately after phagocytosis, total cholesterol levels in both control and A2E-loaded cells increased 3-fold relative to cells that were not fed OS.…”
Section: A2e Causes Endogenous Cholesterol Accumulation In Rpe Cellsmentioning
confidence: 78%
See 1 more Smart Citation
“…We have previously shown that A2E affects neither the binding nor internalization of OS by RPE cells (8). Immediately after phagocytosis, total cholesterol levels in both control and A2E-loaded cells increased 3-fold relative to cells that were not fed OS.…”
Section: A2e Causes Endogenous Cholesterol Accumulation In Rpe Cellsmentioning
confidence: 78%
“…We have previously demonstrated that A2E specifically delays the metabolism of phagocytosed OS lipids by the RPE, whereas lysosomal proteolysis is unaffected (8). Progressive lipid and cholesterol accumulation in the Bruch's membrane beneath the RPE has been identified as a contributing factor to age-related macular degeneration (AMD) (5).…”
Section: Proteins Involved In Cholesterol Traffickingmentioning
confidence: 99%
“…Accumulation of undigested ROS material within the RPE, whether due to mutations in lysosomal proteases (Rakoczy et al 2002) or due to accumulation of natural non-degradative substrates (e.g. lipofuscin, Finnemann et al 2002), similarly causes photoreceptor cell death. Therefore, a tight coupling between photoreceptor outer segment shedding and RPE phagocytosis is necessary for retinal health.…”
Section: Introductionmentioning
confidence: 99%
“…A2E has several potential cytotoxic effects on RPE cells, including destabilization of membranes (19)(20)(21), release of proapoptotic proteins from mitochondria (22,23), sensitization of cells to blue-light damage (24)(25)(26), impaired lysosomal acidification (27), and impaired degradation of phospholipids from phagocytosed outer segments (28). Irradiation of A2E with blue (430-nm) light resulted in a series of oxirane products containing up to nine epoxide rings, formed by addition of singlet oxygen to double bonds along the polyene chains (29).…”
mentioning
confidence: 99%